Management of fibroma on the upper lip and left buccal mucosa: Penatalaksanaan fibroma pada bibir atas dan mukosa bukal kiri - andries pascawinata; Fadil Muhammad Pashya (Makassar Dental Journal, 2023)
Fibroma is a benign tumor of the oral cavity which is generally found on the tongue, gingiva, andbuccal mucosa; usually the result oftrauma, chronic irritation,and hormonal factors. This article is aimed to report the management of 2 cases of fibroma that occurred on the upperlip and buccal mucosa.In case-1,a 25-year-old male came with complaints of a lump on his upperlip 1 month ago.Clinical examination reveale dasessile lump,about 1 cm in diameter. In case-2,a 46-year-old female came with complaints of alump on the left cheek mucosa. Clinical examination found a lump measuring about 1.5cm and sharp toothroots 36. It was performed complete excision in both cases;specific tocase-2,the remaining sharprootsof tooth 36 were extracted. The biopsy results show that the lesion is a fibroma. No recurrence was seen 2 weeks post-treatment.It is concluded that treatment with complete excision in both cases was successful without recurrence.